2000
DOI: 10.1099/00221287-146-9-2325
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the rate-limiting step for the biosynthesis of arachidonic acid in Mortierella alpina is at the level of the 18:3 to 20:3 elongase

Abstract: Mortierella alpina, a fungus used commercially as a source of arachidonic acid, 20 :4(n-6), has been examined to see if growth on lipid-based carbon sources leads to repression of either fatty acid biosynthesis and/or fatty acid desaturation and elongation. Changes in the activities of ATP :citrate lyase, isocitrate lyase, carnitine acetyltransferase, malic enzyme, glucose-6-phosphate dehydrogenase and pyruvate kinase when the fungus was grown on fatty-acid-based (Tween) carbon sources were consistent with (i)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(42 citation statements)
references
References 26 publications
2
39
0
1
Order By: Relevance
“…Lipid was extracted from freeze-dried biomass as previously described (Song et al, 2001) and its amount determined gravimetrically. Fatty acids, as their methyl esters, were prepared and analysed by GC, as described by Wynn & Ratledge (2000).…”
Section: Methodsmentioning
confidence: 99%
“…Lipid was extracted from freeze-dried biomass as previously described (Song et al, 2001) and its amount determined gravimetrically. Fatty acids, as their methyl esters, were prepared and analysed by GC, as described by Wynn & Ratledge (2000).…”
Section: Methodsmentioning
confidence: 99%
“…However, significant advances have been made recently. For instance, evidence from enzymatic studies in the arachidonic acid-producing fungus, M. alpina, have suggested that the C [18][19][20] elongase, rather than Δ6 desaturase, may in fact be the rate-limiting step in the biosynthesis of 20:4n-6 in that organism (Wynn and Ratledge, 2000). Fatty acid elongation is a microsomal process effected in four steps each catalysed by a specific enzyme.…”
Section: Lipogenesismentioning
confidence: 99%
“…Evidently, all AZ diets except ASH5 activated the formation of linoleic acid (C18:1), which in turn was converted to arachidonic acid in a similar way as mentioned in the above. Although the limiting step may reside at elongase for elongation of C18:3 (n = 6) to 20:3 (n = 6) as similarly reported for fungus Mortierella alpina (Mortierellaceae) (Wynn & Ratledge, 2000).…”
Section: Effect Of Alpinia Diets On Major Hepatic Fatty Acidsmentioning
confidence: 75%